Konstruksi Praktik Akuntansi Pengumpulan Dana Zakat berbasis Nilai Diila O’onto, Bo Wolu-Woluwo - Vindi Paputungan; Mohamad Anwar Thalib; Nabila Putri H. Yunginger (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2026)
Purpose: This study aims to construct the practice of zakat fund collection accounting at BAZNAS Gorontalo Regency based on Gorontalo local wisdom values. Method: This study employs a spiritual paradigm with an Islamic ethnomethodology approach. Data were collected through observation, structured interviews, and documentation involving four administrators of BAZNAS Gorontalo Regency. Data analysis was conducted through the stages of charity, knowledge, faith, revealed information, and courtesy. Results: The accounting practices of zakat fund collection are carried out through deposits to BAZNAS bank accounts, deposit facilitation by administrators, collection through Zakat Collection Units (UPZ), salary or employee performance allowance (TPP) deductions for civil servants, regular reporting to the local government, and verification of receipts using bank statements and transfer receipts. These practices reflect the value of amanah (trustworthiness) in zakat fund management. Implications: The study shows that integrating the value of amanah into zakat accounting practices can strengthen transparency, accountability, and public trust in zakat management institutions. Novelty: The novelty of this study lies in the construction of zakat fund collection accounting practices based on the Gorontalo local wisdom value of Diila o’onto, bo wolu-woluwo (unseen yet existing), which interprets visible accounting practices as manifestations of the invisible but real value of amanah.